Photochemistry of 1-phenyl-tetrazolone isolated in solid argon - Gomez Zavaglia, Andrea (2006)
The molecular structure, vibrational spectra, tautomerism and photochemistry of the derivative of tetrazole, 1-phenyl-tetrazolone (C7H6N4O;PT) have been studied by FT-IR matrix isolation spectroscopy and DFT/B3LYP/6-311++G(d,p) calculations. Among the five structures in which PT could be expected to exist (two keto tautomers, one mesoionic olate-form and two different conformers of the hydroxyl tautomer), only the most stable species, 1-phenyl-1,4-dihydro-5H-tetrazol-5-one, could be experimentally observed in low temperature argon matrices. Monomers of this tautomer give rise to an IR spectrum that fits nicely the calculated spectrum obtained at the DFT/B3LYP/6-311++G(d,p) level of theory. In situ UV irradiation (λ > 235 nm) of the matrix-isolated PT induces three main photochemical processes, all of them involving cleavage of the tetrazolering: e.g. (1) molecular nitrogen loss, with production of 1-phenyl- diaziridin-3-one; this compound reacts subsequently to form 1-aza-1,2,4,6- cycloheptatetraene and isocyanic acid (eventually, also to form CO plus phenyldiazene); (2) cleavage of the C(5)–N(1) and N(3)–N(4) tetrazole-ring bonds, with production of phenylazide and isocyanic acid, with phenylazide then losingN2 to yield as final product 1-aza-1,2,4,6-cycloheptatetraene; and (3) cleavage of the N(1)–N(2) and N(4)–C(5) tetrazole-ring bonds, to yield phenylisocyanate and azide. The observed photochemical processes are distinct from the preferred thermal fragmentation channel, where CO is produced together with a weak IR absorbant species.